Diseño y construcción de un teslámetro digital embebido para la caracterización magnética de materiales (2014)
We present the design, construction and validation of an embedded digital teslameter, intended for use in experiments of magnetic materials characterization by inductive and static methods -- The teslameter consists of a planar type Hall effect transducer THS119, with differential output and adjustable measuring range, an INA129P instrumentation amplifier with adjustable gain, a microcontroller PIC16F873A with ADC converter of 10-bits for digital processing, data storage and data transfer to the computer via serial port; and a liquid crystal display to visualize the measurements -- The system is adaptable to magnetic field transducers with single or differential output and with different measuring ranges; is sensitive to changes in the intensity and the polarity of the applied magnetic field and has an effective sensitivity of 5.0 mV/mT and uncertainty of 0.5−3T for the THS119 Hall effect transducer -- The prototype teslameter was compared with a commercial teslameter PHYWE 13610.90